Sport modality affects bradycardia level and its mechanisms of control in professional athletes - Azevedo, L. F.; Perlingeiro, P. S.; Hachul, D. T.; Gomes-Santos, I. L.; Brum, P. C.; Allison, T. G.; Negrão, C. E.; De Matos, L. D. N. J. (International Journal of Sports Medicine, 2014)
We investigated the influence of sport modalities in resting bradycardia and its mechanisms of control in highly trained athletes. In addition, the relationships between bradycardia mechanisms and cardiac structural adaptations were tested. Professional male athletes (13 runners, 11 cyclists) were evaluated. Heart rate (HR) was recorded at rest on beat-to-beat basis (ECG). Selective pharmacological blockade was performed with atropine and esmolol. Vagal effect, intrinsic heart rate (IHR), parasympathetic (n) and sympathetic (m) modulations, autonomic influence (AI) and autonomic balance (Abal) were calculated. Plasmatic norepinephrine (high-pressure liquid chromatography) and cardiac structural adaptations (echocardiography) were evaluated. Runners presented lower resting HR, higher vagal effect, parasympathetic modulation (n), AI and IHR than cyclists (P<0.05). Abal, sympathetic modulation (m) and norepinephrine level were similar within athletes regardless of modality. The cardiac chambers were also similar between runners and cyclists (P=0.30). However, cyclists displayed higher septum and posterior wall thickness than runners (P=0.04). Further analysis showed a trend towards inverse correlation between IHR with septum wall thickness and posterior wall thickness (P=0.056). Type of sport influences the resting bradycardia level and its mechanisms of control in professional athletes. Resting bradycardia in runners is mainly dependent on an autonomic mechanism. In contrast, a cyclist`s resting bradycardia relies on a non-autonomic mechanism probably associated with combined eccentric and concentric hypertrophy.